Patients with systemic sclerosis-associated pulmonary arterial hypertension express a genomic signature distinct from patients with interstitial lung disease. Issue 3 (October 2018) - Moll, Matthew; Christmann, Romy B; Zhang, Yuqing; Whitfield, Michael L; Wang, Yu Mei; Rice, Lisa; Stratton, Eric; Lafyatis, Robert; Farber, Harrison W
Objective: Pulmonary arterial hypertension and interstitial lung disease are major causes of mortality in systemic sclerosis. We used a previously identified microarray biomarker to determine whether systemic sclerosis-pulmonary arterial hypertension and systemic sclerosis-interstitial lung disease patients demonstrate distinct gene expression profiles. Methods: Peripheral blood mononuclear cells were collected from healthy controls ( n = 10), systemic sclerosis patients without pulmonary hypertension (systemic sclerosis-no pulmonary arterial hypertension, n = 39), and systemic sclerosis-pulmonary arterial hypertension patients ( n = 21; mean pulmonary arterial pressure ≥25, pulmonary capillary wedge pressure ≤15, and pulmonary vascular resistance ≥3 Wood units) diagnosed by right heart catheterization. Systemic sclerosis-interstitial lung disease patients were defined as those with evidence of fibrosis on chest computed tomography and significant restriction (forced vital capacity <70% predicted, n = 11). Systemic sclerosis-pulmonary arterial hypertension biomarker included 69 genes selected by unbiased statistical screening of three publicly available microarray studies. RNA levels were measured by NanoString Technologies. Gene expression levels that were significantly correlated with pulmonary arterial hypertension (multiple statistical measures) were chosen as inputs into a forward selection logistic regression model. Results: When interstitial lung disease patients were included ( n = 64), four genes (S100P, CD8B1, CCL2, and TIMP1) and male sex predicted pulmonary arterial hypertension with a high level of accuracy (area under the curve = 0.83). Without interstitial lung disease patients ( n = 53), two genes (THBS1 and CD8B1) and male sex predicted pulmonary arterial hypertension with a high level of accuracy (area under the curve = 0.80). When examining systemic sclerosis patients with borderline elevated pulmonary pressures (mean pulmonary arterial pressure = 21–24 mmHg), gene expression changes closely resembled the systemic sclerosis-pulmonary arterial hypertension group, except for THBS1. Conclusion: Systemic sclerosis-pulmonary arterial hypertension and systemic sclerosis-interstitial lung disease have similar but distinct gene expression profiles. Many gene expression changes occur early in the disease course, potentially allowing early detection. THBS1 appears to be an important mediator in the development of pulmonary arterial hypertension-predominant phenotype. Further prospective investigation is warranted.